Penggunaan Afiks dalam Bahasa Indonesia: Studi Morfologis pada Artikel Berita Online - Saputra, Gede Adistana Wira; Irawan, I Putu Ari Utama; Sucipta, I Made Darma; Fazalani, Runi (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Background The Indonesian language features a complex morphological system, one of which is affixation, playing a crucial role in the formation of meaning and grammatical structure of words. In the context of digital media, the use of affixes in online news texts reflects the dynamic nature of language, which evolves rapidly to meet the demands of modern communication. Objectives: This study aims to describe the forms and functions of affixes in online news articles from two national news portals: Detik.com and Tempo.co. Methods: A qualitative approach with a descriptive morphological method was employed. The data were collected from articles published between February and June 2025 and analyzed to identify the types, frequency, and functions of affixes. . Results: The results indicate that prefixes and confixes are the most dominant types of affixes, accounting for 60% and 30% of total usage respectively, while suffixes make up only 8% and infixes are rarely found. Prefixes such as meN-, di-, and ter- play a significant role in forming informative and efficient sentence structures. Confixes like peN-...-an and ke-...-an are frequently used to convey abstract concepts in economic and political discourse. Conclusion: The study concludes that affixation—particularly through prefixes and confixes—is a primary linguistic strategy in digital journalistic discourse, reflecting the efficiency and clarity of information that modern mass media demands. Keywords : Affixation, morphology, online news, prefixes, confixes